Progression-Specific Genes Identified by Expression Profiling of Matched Ductal Carcinomas In situ and Invasive Breast Tumors, Combining Laser Capture Microdissection and Oligonucleotide Microarray Analysis - Christina S. Schuetz; Michael Bonin; Susan E. Clare; Kay Nieselt; Karl Sotlar; Michael Walter; Tanja Fehm; Erich Solomayer; Olaf Rieß; D. Wallwiener; Raffael Kurek; Hans Neubauer (2006)
Becoming invasive is a crucial step in breast cancer oncogenesis. At this point, a lesion carries the potential for spreading and metastasis--a process, whose molecular characteristics still remain poorly understood. In this article, we describe a matched-pair analysis of ductal carcinoma in situ (DCIS) and invasive ductal carcinoma (IDC) of nine breast ductal carcinomas to identify novel molecular markers characterizing the transition from DCIS to IDC. The purpose of this study was to better understand the molecular biology of this transition and to identify candidate genes whose products might serve as prognostic markers and/or as molecular targets for treatment. To obtain cellular-based gene expression profiles from epithelial tumor cells, we combined laser capture microdissection with a T7-based two-round RNA amplification and Affymetrix oligonucleotide microarray analysis. Altogether, a set of 24 tumor samples was analyzed, comprised of nine matched DCIS/IDC and replicate DCIS/IDC preparations from three of the nine tumors. Cluster analysis on expression data shows the robustness and reproducibility of the techniques we established. Using multiple statistical methods, 546 significantly differentially expressed probe sets were identified. Eighteen candidate genes were evaluated by RT-PCR. Examples of genes already known to be associated with breast cancer invasion are BPAG1, LRRC15, MMP11, and PLAU. The expression of BPAG1, DACT1, GREM1, MEF2C, SART2, and TNFAIP6 was localized to epithelial tumor cells by in situ hybridization and/or immunohistochemistry, confirming the accuracy of laser capture microdissection sampling and microarray analysis.